2018
DOI: 10.14444/5052
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Liposomal Bupivacaine in Lumbar Spine Surgery

Abstract: Background: Postoperative pain management in spine surgery holds unique challenges. The purpose of this study is to determine if the local anesthetic liposomal bupivacaine (LB) reduces the total opioid requirement in the first 3 days following posterior lumbar decompression and fusion (PLDF) surgery for degenerative spondylosis.Methods: Fifty patients underwent PLDF surgery in a prospective randomized control pilot trial between August 2015 and October 2016 and were equally allocated to either a treatment (LB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
(26 reference statements)
1
13
0
Order By: Relevance
“…In terms of opioid use, Tomov et al 14 noted a significant reduction within the immediate postoperative period in their spinal fusion cohort who were treated with LB, which corresponds to our findings within the first 24 postoperative hours. On the other hand, for multiple spinal fusion studies of LB analgesia, 12,14,19 the authors reported no difference in total opioid use by the time of discharge, which parallels our findings after the first 24 postoperative hours to discharge. In terms of pain scores, Brusko et al 13 showed in their spinal fusion cohort that the only significant difference between their LB and control cohorts was on the first postoperative day, with the LB cohort reporting lower scores, but this difference was no longer observed up until discharge, a trend that was also reported by Puffer et al, 19 and both studies ultimately mirror the experiences we report here for the use of LB for pain relief in pediatric patients undergoing Chiari decompression.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In terms of opioid use, Tomov et al 14 noted a significant reduction within the immediate postoperative period in their spinal fusion cohort who were treated with LB, which corresponds to our findings within the first 24 postoperative hours. On the other hand, for multiple spinal fusion studies of LB analgesia, 12,14,19 the authors reported no difference in total opioid use by the time of discharge, which parallels our findings after the first 24 postoperative hours to discharge. In terms of pain scores, Brusko et al 13 showed in their spinal fusion cohort that the only significant difference between their LB and control cohorts was on the first postoperative day, with the LB cohort reporting lower scores, but this difference was no longer observed up until discharge, a trend that was also reported by Puffer et al, 19 and both studies ultimately mirror the experiences we report here for the use of LB for pain relief in pediatric patients undergoing Chiari decompression.…”
Section: Discussionsupporting
confidence: 87%
“…A primary concern surrounding the use of LB in a pediatric cohort is the risk of associated adverse events, particularly in cases in which the central nervous system is exposed to the drug. In large adult series, 9,12 the most common adverse events associated with LB in general are nausea, emesis, constipation, and hypotension events. More specific to neurosurgery and Chiari surgery, central nervous system toxicity has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For subgroup analyses, we identified 5 groups, which included 3 or more trials: nonsteroidal anti-inflammatory drugs (NSAIDs), 3 , 55 , 59 , 62 , 71 epidural analgesia, 2 , 7 , 21 , 32 , 60 ketamine infusion, 1 , 5 , 24 , 41 , 53 , 64 , 66 local infiltration analgesia, 6 , 22 , 44 , 61 and intrathecal (i.t.) morphine.…”
Section: Resultsmentioning
confidence: 99%
“…Four trials reported on local infiltration/wound analgesia and 24-hour opioid consumption. 6 , 22 , 44 , 61 The meta-analysis favored the control group and reported no significant reduction in opioid consumption 2 mg i.v. per 24 hours (95% CI: −5 to 10) with large heterogeneity I 2 = 98% (Fig.…”
Section: Resultsmentioning
confidence: 99%